1999
DOI: 10.1152/ajplung.1999.277.2.l381
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation and cellular localization of fatty acid synthase in human fetal lung

Abstract: Fatty acid synthase (FAS; EC 2.3.1.85 ) supplies de novo fatty acids for pulmonary surfactant synthesis, and FAS gene expression is both developmentally and hormonally regulated in the fetal lung. To further examine hormonal regulation of FAS mRNA and to determine the cellular localization of FAS gene expression, we cultured human fetal lungs (18–22 wk gestation) as explants for 1–4 days in the absence (control) or presence of glucocorticoid [dexamethasone (Dex), 10 nM] and/or cAMP agents (8-bromo-cAMP, 0.1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
1
18
0
2
Order By: Relevance
“…Our findings that dexamethasone alone strongly induces SPs in lung explants (3), but not in isolated epithelial cells, highlight the critical role of cAMP. Previous studies with fetal lung explants found stimulatory effects of cAMP analogs (5) and synergism with glucocorticoids on phospholipid synthesis (27), formation of lamellar bodies (46), and induction of SPs (39,40) and fatty acid synthase (61). Our present studies in cultured cells indicate a more extensive role of cAMP than previously surmised from explant studies.…”
Section: Discussionsupporting
confidence: 59%
“…Our findings that dexamethasone alone strongly induces SPs in lung explants (3), but not in isolated epithelial cells, highlight the critical role of cAMP. Previous studies with fetal lung explants found stimulatory effects of cAMP analogs (5) and synergism with glucocorticoids on phospholipid synthesis (27), formation of lamellar bodies (46), and induction of SPs (39,40) and fatty acid synthase (61). Our present studies in cultured cells indicate a more extensive role of cAMP than previously surmised from explant studies.…”
Section: Discussionsupporting
confidence: 59%
“…It is well established that catecholamines exert major metabolic effects, which could finally culminate in enhanced lipogenesis and lipid overload: Catecholamines induce inappropriate FFA use by triggering (i) an increase in serum levels of FFAs, (ii) wasteful cycling of FFAs through enhanced intramyocardial lipolysis, and (iii) FFA-mediated suppression of glucose metabolism [41]. Concomitantly, catecholamines increase the RNA stability of FASN [42], and trigger UCP1 gene expression via β-adrenergic receptor-mediated stimulation of cAMP [43]. Apart from over-activation of the adrenergic system, the angiotensin II AT1 receptor, another key player in the development of heart failure, also up-regulates the cardiac fat metabolism by increasing the expression of FASN [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal lung parenchyma was minced into 1-mm 3 pieces and placed in organ culture, as described previously (40). Briefly, tissue pieces were distributed in two parallel strips on 60-mm culture dishes placed on a platform that rocks (3 oscillations/min) to expose the explants alternately to serum-free Waymouth medium (2 ml/dish) or an atmosphere of 95% air, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%